Cover Picture: Electrocatalytic SiC Nanoparticles/PEDOT:PSS Composite Thin Films as the Counter Electrodes of Dye‐Sensitized Solar Cells (ChemElectroChem 6/2014). Issue 6 (11th June 2014) - Tsai, Yu‐Lin; Li, Chun‐Ting; Huang, Tzu‐Yen; Lee, Chi‐Ta; Lin, Chen‐Yang; Chu, Chih‐Wei; Vittal, R.; Ho, Kuo‐Chuan
<x xml:space="preserve">Abstract</x> The front cover artwork was chosen to show a composite film of silicon carbide nanoparticles and poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) as the counter‐electrode material for a dye‐sensitized solar cell. The optimized composite provides a good overall electrocatalytic ability, a reasonable intrinsic heterogeneous rate constant, a large effective electrocatalytic surface area, and a high cell efficiency. (DOI: 10.1002/celc.201300242).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>